The Brazilian health system at crossroads: progress, crisis and resilience. Issue 4 (3rd July 2018) - Massuda, Adriano; Hone, Thomas; Leles, Fernando Antonio Gomes; de Castro, Marcia C; Atun, Rifat
Abstract : The Unified Health System (Sistema Único de Saúde (SUS)) has enabled substantial progress towards Universal Health Coverage (UHC) in Brazil. However, structural weakness, economic and political crises and austerity policies that have capped public expenditure growth are threatening its sustainability and outcomes. This paper analyses the Brazilian health system progress since 2000 and the current and potential effects of the coalescing economic and political crises and the subsequent austerity policies. We use literature review, policy analysis and secondary data from governmental sources in 2000–2017 to examine changes in political and economic context, health financing, health resources and healthcare service coverage in SUS. We find that, despite a favourable context, which enabled expansion of UHC from 2003 to 2014, structural problems persist in SUS, including gaps in organisation and governance, low public funding and suboptimal resource allocation. Consequently, large regional disparities exist in access to healthcare services and health outcomes, with poorer regions and lower socioeconomic population groups disadvantaged the most. These structural problems and disparities will likely worsen with the austerity measures introduced by the current government, and risk reversing the achievements of SUS in improving population health outcomes. The speed at which adverse effects of the current and political crises are manifested in the Brazilian health system underscores the importance of enhancing health system resilience to counteract external shocks (such as economic and political crises) and internal shocks (such as sector-specific austerity policies and rapid ageing leading to rise in disease burden) to protect hard-achieved progress towards UHC.